Assessment of muscle fiber types transformation in rats with discogenic low back pain using diffusion tensor image of paraspinal muscles - Ying Wu; Jiyao Ma; Yilong Huang; Zhenguang Zhang; Jiangyuan Pi; Chao Gao; Wenyang Leng; Bo He (BMC Medical Imaging)
Abstract Background The onset of discogenic lower back pain (DLBP) was strongly associated with fiber-type transformation in the paraspinal muscles. Management of DLBP would be greatly benefited from an objective, noninvasive biomarker for assessing fiber composition. Our study aimed to explore the value of diffusion tensor imaging (DTI) in evaluating fiber-type transformation, which contributed to improve diagnosis and intervention strategies on DLBP. Methods According to time since model establishment, ninety healthy female Sprague Dawley rats were randomly divided into the 1st month group,3rd month group, and 6th month group, then each group was subdivided into the DLBP group, sham-operated group, and control group. The L4/5 and L5/6 intervertebral discs of rats underwent posterior-entry puncture disruption and sham-operation to establish DLBP and sham-operation groups. DTI MRI and immunofluorescence (IF) were performed to assess fiber type transformation. Results The DLBP rats exhibited a gradual decrease in Fractional Anisotropy (FA) values. At the 3rd month and 6th month after modeling, there was a significant decrease in the percentage of type I fiber, while an increase in the percentage of type II fiber. Notably, the percentage of type I fiber demonstrated a moderate positive correlation with FA values. Conclusion DTI may serve as a potential tool to investigate the fiber type transformation in DLBP rats. Clinical trial number Not applicable.